Strategi Mindfulness melalui Kegiatan Yoga untuk Emotional Self-Control pada Anak - Aisyah Putri Sulistyaningrum; Yuli Kurniawati Sugiyo Pranoto (UNIB Press, 2026)
Abstract: Early childhood requires optimal stimulation in social-emotional development, including emotional self-control skills. However, some children still experience difficulties in regulating their emotions. This study aims to analyze the implementation of mindfulness strategies through yoga activities in supporting the emotional self-control of children aged 4–6 years. This research employed a qualitative approach with a case study design conducted at KB-TK Lab UM Malang. Data were collected through observation, semi-structured interviews, and documentation. The findings revealed that yoga activities were implemented systematically as part of the Merdeka Curriculum through simple physical movements, breathing exercises, and concentration practices that helped children become calmer, more focused, and better able to regulate their emotions. Supporting factors included school support, teachers’ understanding of mindfulness practices, adequate facilities and infrastructure, and the involvement of teaching assistant students. Meanwhile, the challenges identified were limited time allocation and the diverse emotional conditions of children, which resulted in inconsistent implementation of the activities. Keywords: Mindfulness, Yoga, Emotional Self-Control, Early Childhood Education.